Fiber reinforced concrete. Part II: Application - Valente, T. D. S. (2017)
The present paper is the second part of two companion papers related with the design and application of fiber reinforced concrete (FRC) in structural elements. It is presented a case study regarding the use of FRC in the development and construction of a new sustainable building system based on the assembly of structural prefabricated sandwich panels formed by thin outer layers of steel fiber reinforced self-compacting concrete (SFRSCC) and an insulation core. The outer layers of SFRSCC are connected with innovative glass fiber reinforced polymer (GFRP) connectors. The structural concept is presented and the numerical and experimental work carried out for the construction of a real scale prototype is briefly described